2008
DOI: 10.2337/dc07-1926
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Diabetic Retinopathy in Type 2 Diabetes Is Related to Coronary Artery Calcium in the Veterans Affairs Diabetes Trial (VADT)

Abstract: OBJECTIVE -Increasing evidence suggests that macrovascular disease and retinopathy may be more closely linked than previously believed. We determined the relationship between retinopathy and coronary atherosclerosis as measured by computed tomography-detectable coronary artery calcium (CAC).RESEARCH DESIGN AND METHODS -The cross-sectional association between CAC and retinopathy was assessed on a Veteran Affairs Diabetes Trial subsample of 204 subjects with a mean duration of type 2 diabetes of 12.3 Ϯ 8.3 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 44 publications
2
22
0
1
Order By: Relevance
“…Literature is now available to show that retinopathy predicts CV mortality in type 2 diabetes [33]. A cross-sectional association between coronary artery calcium (CAC) and proliferative diabetic retinopathy has been reported in a VADT subsample of diabetic patients [34]. Of note, the association remained statistically significant even after adjustment for multiple CV risk factors.…”
Section: Hypoglycaemia: a Trigger For CV Events?mentioning
confidence: 99%
“…Literature is now available to show that retinopathy predicts CV mortality in type 2 diabetes [33]. A cross-sectional association between coronary artery calcium (CAC) and proliferative diabetic retinopathy has been reported in a VADT subsample of diabetic patients [34]. Of note, the association remained statistically significant even after adjustment for multiple CV risk factors.…”
Section: Hypoglycaemia: a Trigger For CV Events?mentioning
confidence: 99%
“…The early application of digital retinal photographs or fluorescein angiography can help physicians and ophthalmologists to screen for DR and determine its severity in patients with DM. Plenty of studies have reported that DR has a close relationship with CVD [15][16][17][18][19], and PAD, a subclinical CVD, is significantly associated with DR [20].…”
mentioning
confidence: 99%
“…(22) Results from the VADT and ACCORD suggested that intensive glucose control therapy in diabetic patients with a long duration of diabetes and preexisting CVDs had either no effect or was even detrimental in terms of cardiovascular and cerebrovascular outcomes. (23,24) Intensive glucose control therapy has inherent defects. (26,27) In fact, the targeted rates of blood glucose is very low all over the world in patients with diabetes melitus and most patients are actually in a constant state of hyperglycemia.…”
Section: Paradox Of Intensive Lowering Of Glucose and Preventing Cardmentioning
confidence: 99%